2018
DOI: 10.9778/cmajo.20180029
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and liver transplantation burden of primary biliary cholangitis: a retrospective cohort study

Abstract: rimary biliary cholangitis (PBC) is a rare chronic autoimmune cholestatic liver disease characterized by destruction of the small intrahepatic bile ducts. It predominantly affects middle-aged and elderly women. 1,2 Despite its rarity, PBC is an important cause of liver-related morbidity. 2-5 In the United States, the annual economic burden of PBC has been estimated to be $69-$115 million. 3 There is concern that the economic impact of PBC could increase significantly in the future because of the increasing inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In South Korea, while the incidence of AIH was stable, the prevalence increased gradually from 2009 to 2013 . Rising prevalence of PBC over time has consistently been reported from the Netherlands, northern Italy and Denmark, Hong Kong, Canada, and the USA, and it is a point of debate whether the incidence of PBC is also increasing. In PSC, two systematic reviews concluded that the prevalence as well as the incidence of PSC seem to be increasing .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Korea, while the incidence of AIH was stable, the prevalence increased gradually from 2009 to 2013 . Rising prevalence of PBC over time has consistently been reported from the Netherlands, northern Italy and Denmark, Hong Kong, Canada, and the USA, and it is a point of debate whether the incidence of PBC is also increasing. In PSC, two systematic reviews concluded that the prevalence as well as the incidence of PSC seem to be increasing .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Estimation of prevalence of AILDs is critical to assess the burden of these diseases on public health. A number of epidemiological studies have been undertaken for AIH, [9][10][11][12][13][14][15][16][17][18][19] PBC, 13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and PSC [37][38][39][40][41][42][43] worldwide, and have shown that prevalence significantly varies depending on regions and ethnicities. Interestingly, several recent studies have indicated that prevalence of all three AILDs has been increasing over the years.…”
Section: Introductionmentioning
confidence: 99%
“…Primary biliary cholangitis (PBC) is an uncommon chronic cholestatic liver disease with an estimated prevalence of 318 per million people in Canada. ( 1 ) The disease is characterized by progressive destruction of interlobular bile ducts and is clinically impactful with an increased risk of progression to advanced biliary fibrosis, end‐stage liver disease, and death. Until recently, ursodeoxycholic acid (UDCA) was the only approved therapy widely accepted to improve clinical outcomes in patients with PBC ( 2,3 ) ; however, approximately 40% of patients have incomplete biochemical response to UDCA and remain at risk of disease progression.…”
mentioning
confidence: 99%
“…After careful examination of the full texts, five studies were excluded because of duplicate reports for the same subjects, reports unrelated to prevalence of PBC, and no data on prevalence or incidence for PBC. Twenty-four studies were thus included in this systematic review [5][6][7][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]30] , which comprises 22 studies based on cases and 2 based on general population (Figure 1). Among 327 studies published in Chinese (searched in Chinese database), 4 based on general population were selected and no papers based on cases were found [28,29,31,32] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…USA 2010-2013 6107 -adults --Kim et al [18] , [19] , 897/2073 -Lleo et al [19] , [20] , 2017 Gatselis et al [6] , Cheung et al [21] , Non-whit Wahlin et al [7] , [23] , [24] , 2018 Yoshida et al [25] , [26] , Myers et al [9] , Chong et al [10] , Baldursdottir et al [11] , 2012…”
mentioning
confidence: 99%